DEVELOPMENT OF A BLUETOOTH-BASED WIRELESS STETHOSCOPE WITH MUSIC FEATURES TO REDUCE TODDLER ANXIETY - Nyak Qurratu Aini; Gianina Inaya; Rafli Hamdan Farabi; Zulhiz Tami; Rafles Nobel Pangaribuan; Kartika (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Auscultation examinations in toddlers are often hampered by psychological responses such as fear, anxiety, and rejection of the stethoscope, making it difficult to guide the child and resulting in a less than optimal diagnosis process. This study aims to develop a child-friendly Bluetooth-based electronic stethoscope with additional music features as audio distractions to improve comfort and reduce anxiety in toddlers during medical examinations. The research method uses a research and development approach that includes electronic system design, prototype creation, audio testing, and device performance evaluation. The prototype was designed with a microphone signal amplifier system integrated with a Bluetooth module for wireless transmission to a headset and music player module. The test results showed that the use of this stethoscope was able to create a calmer examination atmosphere, marked by reduced resistance and excessive movement in toddlers during auscultation. The music feature proved to be a positive distraction that increased the child's comfort and cooperation. In addition, physiological sounds such as heartbeat and breathing remain clearly audible through the wireless connection without latency interference. This innovation has the potential to be a child-friendly auscultation solution that improves the comfort of infant patients and the effectiveness of medical examinations